Research status of essential oils extracted from Philippine plants [Review paper] - Uñalivia, Felicisima D. (1984)
This is a brief discussion of natural products research on essential oils, which includes its objectives and importance, and the research studies currently going on at the Pharmaceutical and Cosmetic Product Development Program of the Institute of Science and Technology.
Includes bibliographical references (pages 228-229) and index.
Keywords: Chemistry; Essential Oils -- Research status